Dyspnea and COVID-19: A Review of Confounding Diagnoses during the Postpartum Period - Clara Nunes Castro; Pedro Paulo Machado Lopes; Jussara Mayrink (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract The puerperium is a complex period that begins with placental delivery and lasts for 6 weeks, during which readaptation of the female organism and redistribution of blood volume occur. This period is conducive to the occurrence of thromboembolic events. In the context of the SARS-CoV-2 pandemic, the virus responsible for COVID-19, the attention of the scientific community and health professionals has been focused on obtaining insights on different aspects of this disease, including etiology, transmission, diagnosis, and treatment. Regarding the pregnancy-postpartum cycle, it is opportune to review the clinical conditions that can occur during this period and to investigate dyspnea as a postpartum symptom in order to avoid its immediate association with COVID-19 without further investigation, which can lead to overlooking the diagnosis of other important and occasionally fatal conditions.